CT and MR Imaging Features of Primary Central Nervous System Lymphoma in Norway, 1989–2003 - Haldorsen, I.S.; Kråkenes, J.; Krossnes, B.K.; Mella, O.; Espeland, A. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: Studying imaging findings of non–acquired immunodeficiency syndrome (AIDS) primary central nervous system lymphoma (PCNSL), we hypothesized that the imaging presentation has changed with the increasing incidence of PCNSL and is related to clinical factors (eg, time to diagnosis and the patient's being diagnosed alive or at postmortem examination).MATERIALS AND METHODS: Chart and histologic reviews of patients recorded as having PCNSL during 1989–2003 in the Norwegian Cancer Registry identified 98 patients with non-AIDS PCNSL; 75 had available imaging. CT and MR images from the first diagnostic work-up after onset of symptoms but before histologic diagnosis were reviewed.RESULTS: CT and/or MR imaging in the 75 patients revealed no lesion in 10 (13%), a single focal lesion in 34 (45%), multiple focal lesions in 26 (35%), and disseminated lesions in 5 (7%) patients. All together, we identified 103 focal lesions (single/multiple): 63% in white matter, 56% abutting the ventricular surface, and 43% in the frontal lobes); 100% (102/102 lesions evaluated with contrast) showed contrast enhancement. The median time from imaging to diagnosis for patients with no, single, multiple, or disseminated lesions was 32, 3, 5, and 3 weeks, respectively (P = .01). Patients with no or disseminated lesions were more often diagnosed at postmortem examination (P = .06). Imaging findings were practically unchanged during the consecutive 5-year periods.CONCLUSIONS: White matter periventricular contrast-enhancing single or multiple focal lesions were typical of non-AIDS PCNSL. No or disseminated lesions heightened the risk of delayed or postmortem diagnosis. Although the incidence of non-AIDS PCNSL has increased, its presentation at imaging remains unchanged.